지방자치단체 주민참여의식 분석과 평가, Analysis on the Local Residents' Consciousness of Participation and the Direction of Policies - 고승희 (한국콘텐츠학회논문지, 충남연구원, 2015)
본 연구는 지역주민들의 지방자치에 대한 인식과 더불어 지방자치 주체들의 참여와 관련한 기본적 기능에 대한 인식, 그리고 주민들의 참여인식과 의지를 분석하고 주민참여를 위한 정책방향을 찾고자 하였다. 분석결과 지방자치에 대한 인식과 주민참여제도 및 의견수렴에 있어 긍정적인 응답이 낮게 나타나고 있었다. 주민들의 참여는 정책의 갈등을 줄이고 성과를 높일 수 있으며 주민들에게는 지역에 대한 관심과 개인적 정치참여를 통한 행복감을 높여 줄 수 있다. 우리나라의 지방자치가 지속적이고 안정적으로 성장할 수 있도록 주민참여에 대한 인식전환에서부터 효율적 제도운영까지 다양한 문제들에 대하여 재점검과 개선의 노력이 요구된다. This study aimed not only to analyze local residents' awareness of local government, basic functions related to local government main agent's participation, and residents' consciousness/will of participation, but also to seek for the policy direction for the residents' participation. In the results of the analysis, the positive responses to the awareness of local government, residents participation system, and the collection of opinions were low. The residents' participation can reduce the conflict of policies and increase the outcomes while it can also increase the residents' happiness through their interest in the region and personal participation in politics. In order to continuously and stably develop the local self-governing system in Korea, it is required to put efforts into reviewing and improving various issues like the change in the awareness of residents' participation and efficient management of the system.
Keywords: 지방자치; 주민참여. 의견수렴; Local Government; Residents' Participation; Awareness of Local Government